The Use of Sensitivity Analysis to Find Maximum Profit in The Production Of Msme Angga Furniture Using The Simplex Method - Dwita Septiani; Iswan Rina; Nurweni Putri; Aulia Oktavia (CIB Nusantara, 2025)
At time progresses, business competition becomes increasingly fierce. This also result in MSME (Micro,small dan Medium Enterprises from various cities competing fiercely. There are many MSME's that have emerged, one of which is Angga Furniture MSME which operates in the furniture sector. The aim of this research is to determine the maximum profit obtained using the Simplex Method and continue with Sensitivity Analysis to see to what extent the objective function coefficients and constants on the right side of the constraint function can change without affecting the optimal solution. Based on calculation using the Simple Method, a maximum sales profit of IDR 2.830.000 is obtained if production is increased for 10 baby swings, 9 capsule chairs and 2 room deviders. Furthermore, using Sensitivity Analysis calculations, the maximum sales profit is IDR 2.454.000 and the maximum sales profit is IDR 4.396.000.